2022
DOI: 10.3390/insects13100866
|View full text |Cite
|
Sign up to set email alerts
|

Females of Halyomorpha halys (Hemiptera: Pentatomidae) Experience a Facultative Reproductive Diapause in Northern Greece

Abstract: Halyomorpha halys (Stål) (Hemiptera: Pentatomidae) is a native pest of East Asia that overwinters as an adult in natural and human-made structures. Adult emergence from overwintering sites starts in spring, whereas females produce offspring in early summer on host plants, where most feeding occurs. In this study, we investigated the reproductive physiology of overwintering females of H. halys in Northern Greece, by determining the duration of the preoviposition period and fecundity of individuals that were le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In the current study, H. halys individuals captured with traps were fewer in 2021 than in 2022, possibly due to the fact that there was a spring frost early in the season in 2021, which reduced host plant fruit set [ 61 ] and consequently affected the development of H. halys populations throughout the growing season [ 62 ]. The presence of adult H. halys populations and nymphs later in the season and especially after harvest suggests that adults may overwinter in or near orchards [ 30 , 63 , 64 ]. These results are very important considering that the study sites were geographically distributed among locations with different climates and topography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, H. halys individuals captured with traps were fewer in 2021 than in 2022, possibly due to the fact that there was a spring frost early in the season in 2021, which reduced host plant fruit set [ 61 ] and consequently affected the development of H. halys populations throughout the growing season [ 62 ]. The presence of adult H. halys populations and nymphs later in the season and especially after harvest suggests that adults may overwinter in or near orchards [ 30 , 63 , 64 ]. These results are very important considering that the study sites were geographically distributed among locations with different climates and topography.…”
Section: Discussionmentioning
confidence: 99%
“…However, few articles describe its overwintering ecology in its native range [ 25 ] and report in isolated and general observations that adults can overwinter in ground litter and inside tree holes [ 26 ], under tree bark [ 27 , 28 ], and in dry, high-elevation mountains [ 17 , 29 ]. In Northern Greece in particular, H. halys has been reported to experience facultative reproductive diapause during unfavourable conditions [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary observations on about 11,000 overwintering adults, collected during autumn of 2018, showed that BMSBs need seven weeks of winter diapause in outdoor conditions, followed by a three-week postdiapause period in controlled conditions before oviposition. While the postdiapause period is essential for females to reach sexual maturity, nothing is known yet about males [ 21 , 22 , 23 ]. However, we hypothesise that a postdiapause period may also be necessary for males to reach sexual maturity, as irradiation during diapause could have stronger effects on sterility than irradiation after this period, which we know lasts three weeks in females.…”
Section: Introductionmentioning
confidence: 99%